Magnetization collapse in polycrystalline YBCO under transport current cycles - Nieva, Gladys (2006)
Fil: Luzuriaga, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina